Comprehensive functional analysis and mapping of SSR markers in the chickpea genome (Cicer arietinum L.). (February 2020) - Asadi, AliAkbar; Ebrahimi, Amin; Rashidi-Monfared, Sajad; Basiri, Mohammad; Akbari-Afjani, Javad
Graphical abstract: Highlights: Uniformity testing showed that the frequency distribution of the gSSRs was uniformly across the eight chickpea chromosomes. A total of 1798 simple sequence repeats (SSRs) containing transcript assembly contigs (TACs) were mapped onto chickpea chromosomes. The chromosomal location and distribution of TAC-SSRs appeared to be unevenly dispersed across the chickpea genome. Transcription regulation proteins were identified for 13.44% of SSR-containing TACs (253 TAC-SSRs). The maximum number of TAC-SSRs (56.6% or 141 TAC-SSRs) was observed in genes encoding proteins that play a common role in various stresses. Abstract: Plant molecular breeding largely depends on the relationship between molecular markers and major traits. Herein, a total of 32, 962 genomic simple sequence repeats (SSRs) were detected in the whole genome of chickpea with an average density of 94.93 SSRs/Mb. Chickpea chromosomes uniformity test indicated that the genomic SSRs (gSSRs) were steadily distributed across the genome. Moreover, 48, 667 transcriptome sequences were analyzed and 1949 SSR-containing transcript assembly contigs (TACs) were identified. The analysis showed that di- and trinucleotide SSRs were the most frequent SSR motifs within the transcriptome sequences. Among them, AT and TTA and AG and TTC motifs within the transcriptome showed the highest frequencies among di- and trinucleotide repeat motifs, respectively. The SSRs-containing TACs were compared to the GenBank non-redundant database using BLASTX, and subsequently, gene ontology (GO) analysis was performed using QuickGO browser to reduce complexity and highlight biological processes associated with the SSRs-containing TACs. The identified SSRs-containing TACs were categorized into 35 enriched functional-related gene group. The mapping of characterized SSRs-containing TACs onto chickpea chromosomes was performed using BLASTN. The mapping result showed that, a total of 1798 SSRs-containing TACs were mapped onto the chickpea genome. Based on the functional analysis result, 249 and 242 of the mapped SSRs-containing TACs were found in the genes encoding for putative stress-related proteins and transcription factors, respectively. The results presented here can be applied to improve and speed up the chickpea breeding programs.